Malaria in Kakuma refugee camp, Turkana, Kenya: facilitation of Anopheles arabiensis vector populations by installed water distribution and catchment systems - Cetron Martin S; Armstrong Gregory L; Burke Heather; Williams Holly A; Koros Dan; Walker Edward D; Engoki Sammy C; Sang David; Ombok Maurice; Akhwale Willis; Nabie Bayoh M; Weinberg Michelle; et al. (Malaria Journal, 2011)
Abstract Background Malaria is a major health concern for displaced persons occupying refugee camps in sub-Saharan Africa, yet there is little information on the incidence of infection and nature of transmission in these settings. Kakuma Refugee Camp, located in a dry area of north-western Kenya, has hosted ca. 60,000 to 90,000 refugees since 1992, primarily from Sudan and Somalia. The purpose of this study was to investigate malaria prevalence and attack rate and sources of Anopheles vectors in Kakuma refugee camp, in 2005-2006, after a malaria epidemic was observed by staff at camp clinics. Methods Malaria prevalence and attack rate was estimated from cases of fever presenting to camp clinics and the hospital in August 2005, using rapid diagnostic tests and microscopy of blood smears. Larval habitats of vectors were sampled and mapped. Houses were sampled for adult vectors using the pyrethrum knockdown spray method, and mapped. Vectors were identified to species level and their infection with Plasmodium falciparum determined. Results Prevalence of febrile illness with P. falciparum was highest among the 5 to 17 year olds (62.4%) while malaria attack rate was highest among the two to 4 year olds (5.2/1,000/day). Infected individuals were spatially concentrated in three of the 11 residential zones of the camp. The indoor densities of Anopheles arabiensis, the sole malaria vector, were similar during the wet and dry seasons, but were distributed in an aggregated fashion and predominantly in the same zones where malaria attack rates were high. Larval habitats and larval populations were also concentrated in these zones. Larval habitats were man-made pits of water associated with tap-stands installed as the water delivery system to residents with year round availability in the camp. Three percent of A. arabiensis adult females were infected with P. falciparum sporozoites in the rainy season. Conclusions Malaria in Kakuma refugee camp was due mainly to infection with P. falciparum and showed a hyperendemic age-prevalence profile, in an area with otherwise low risk of malaria given prevailing climate. Transmission was sustained by A. arabiensis, whose populations were facilitated by installation of man-made water distribution and catchment systems.